CULTURAL PERCEPTIONS OF NOCTURNAL ENURESIS AND THEIR IMPLICATIONS FOR CHILDREN’S WELLBEING AMONG THE EGGON OF NASARAWA STATE, NIGERIA - Bage-John, Dorothy Akpovye (African Journal of Social and Behavioural Sciences, 2026)
Belief systems and traditions are unique to a group of people who share ethnic social bonds and ties, such as language, norms and values. This keeps the social group together and defines their social identity by giving them a sense of belonging. This research used a purely descriptive research design, employing qualitative techniques through In-depth interviews (IDIs) and Key Informant Interviews (KIIs). The study was anchored on three research questions as follows: What is the Eggon cultural perception of bedwetting among children? How does bedwetting affect the well-being of Eggon children? And what traditional actions are taken to stop bedwetting among Eggon children? Both primary and secondary data were collected and analyzed. Gatekeepers, the elderly and community leaders of the Eggon ethnic group were purposively selected to constitute a sample size of 65 interviewees. Sixty-five (65) interviews (KII and IDI) (5) per Local Government Area were conducted. The study was situated in a culture-bound syndromes theory. Data were analysed, and findings revealed that the Eggon cultural perception of bedwetting among children has a spiritual, psychological, social and cultural dimension, which affects the well-being of children. The termite-hill treatment based on the Eggon cultural beliefs, which has spiritual, psychological, social and cultural implications, is the major traditional action taken to handle the problem of bedwetting among Eggon children. The study recommends health enlightenment programs on medical causes of bedwetting by health personnel, to enhance the wellbeing of children in society.